Collapse fragility due to near-field directivity ground motions: Influence of component, rupture distance, hypocenter location. (December 2021) - Veggalam, Sahithi; Karthik Reddy, K.S.K.; Somala, Surendra Nadh
Abstract: The variability in source characteristics induces spatial variability in the characteristics of near-field ground motion intensities which in turn impacts the fragility behaviour of structures. The study aims to quantify such variability in fragility curves of low-rise structures with a natural period of 0.2 sec with change in nucleation asperity, a source parameter of earthquake rupture corresponding to (Mw ⋍ 7). Four rupture scenarios are considered which differ from each other based on the position of nucleation asperity. The rupture scenarios are termed as bilateral, partial bilateral, partial unilateral, and unilateral, respectively. For bilateral rupture, the nucleation asperity is placed exactly in the middle of the fault face. In contrast, in the unilateral case, the nucleation asperity is placed at the end of the fault. Additionally, fragility curves corresponding to each horizontal component (fault-parallel and fault-normal) of ground motions at stations with varying rupture distances are also highlighted. The study is also extended to evaluate structures' fragility behaviour with a natural period of 0.6 sec, 1 sec and 4 sec. Additionally bi-directional response to the simulated ground motions were emphasized.